2001
DOI: 10.1146/annurev.matsci.31.1.265
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Spinel Ferrite Thin Films

Abstract: ▪ Abstract  Recently there have been significant advances in understanding the magnetic properties of epitaxial ferrite films that are not found in bulk ferrites. Much effort has been expended on trying to achieve bulk properties in thin films for a wide range of applications. From a fundamental science perspective, epitaxial thin films and heterostructures have provided model systems in which novel phenomena, such as modified super-exchange interactions, nearly ideal exchange coupling, and perpendicular excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
111
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(121 citation statements)
references
References 61 publications
7
111
0
3
Order By: Relevance
“…The magnetization values were normalized to the volume fraction of the CFO phase in the BFO/BFO-CFO heterostructure. The shapes of both the inplane and out-of-plane M-H hysteresis loops were found to be similar to that previously reported for self-assembled BFO-CFO and single phase CFO films, [37][38][39][40] with similar values of the coercive field H C . Note that CFO forms a matrix phase in the BFO-CFO template layer on (111) STO.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…The magnetization values were normalized to the volume fraction of the CFO phase in the BFO/BFO-CFO heterostructure. The shapes of both the inplane and out-of-plane M-H hysteresis loops were found to be similar to that previously reported for self-assembled BFO-CFO and single phase CFO films, [37][38][39][40] with similar values of the coercive field H C . Note that CFO forms a matrix phase in the BFO-CFO template layer on (111) STO.…”
supporting
confidence: 85%
“…Since CFO has a significant negative magnetostriction, the magnetoelastic energy will tend to dominate, favoring the in-plane direction to be the easy axis. [37][38][39][40] However, the presence of a small anisotropy between the in-plane and out-of-plane directions is likely due to a small residual strain in the layers. Interestingly, the top BFO layer did not alter the strain state of the BFO-CFO template, and had negligible effect on its magnetic properties.…”
mentioning
confidence: 99%
“…31 In highly strained epitaxial films, magnetic dead layer will be exist at the interface region because of the unrelaxed strain. 32 This magnetic dead layer with small net magnetization will act as the "AFM layer," which pin the spins of magnetic CFO at their interface. Therefore, this restricted rotation and movement of magnetic domain pinned by the dead layer in the interface give rise to the exchange bias and the increased coercive field.…”
Section: Strain-dependent Magnetic Propertiesmentioning
confidence: 99%
“…Suzuki et al 37,38 previously reported that the exchange constant A int , which is the measure of the strength of the exchange coupling, strongly depends on the crystallinity of the magnetic bilayer system. In their report, they discussed A int of the single-crystalline sample with no grain mixture and the polycrystalline sample with significant grain mixturing.…”
Section: The Effect Of Copt Crystallinity and Grain Texturing On Propmentioning
confidence: 99%